2020
DOI: 10.1021/acs.jafc.0c02060
|View full text |Cite
|
Sign up to set email alerts
|

Tripeptides Val-Pro-Pro (VPP) and Ile-Pro-Pro (IPP) Regulate the Proliferation and Migration of Vascular Smooth Muscle Cells by Interfering Ang II-Induced Human Umbilical Vein Endothelial Cells Derived EVs Delivering RNAs to VSMCs in the Co-culture Model

Abstract: Angiotensin II (Ang II), a vasoactive factor in the renin−angiotensin−aldosterone system (RAAS), can regulate vasoconstriction and promote multiple vascular diseases. In this study, the effects of potent antihypertensive peptide Val-Pro-Pro (VPP) and Ile-Pro-Pro (IPP) on the proliferation and migration of vascular smooth muscle cells (VSMCs) by extracellular vesicles (EVs) from vascular endothelial cells (VECs) were studied using a cell co-culture model. The VEC-derived EVs were isolated, characterized, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Importantly, the antagonistic effect of tripeptide LSW on Ang II could be extended by this signal medium. Based on previous research in our laboratory, , we had sufficient evidence to speculate that the extracellular vesicles (EVs) might be responsible for this process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, the antagonistic effect of tripeptide LSW on Ang II could be extended by this signal medium. Based on previous research in our laboratory, , we had sufficient evidence to speculate that the extracellular vesicles (EVs) might be responsible for this process.…”
Section: Resultsmentioning
confidence: 99%
“…EVs have been recognized as an important bridge between VSMCs and VECs to maintain vascular homeostasis by transferring nucleic acids, proteins, and lipids . Recently, our lab has verified that Ang II, being an endogenous octapeptide, can convert the function of vascular cell-derived EVs; foremost, the EVs from Ang II-induced VSMCs or VECs could promote inflammatory and endothelial dysfunction in the recipient cells. , In this study, we tried to analyze the transcriptional differences of the two kinds of EVs from VSMCs with Ang II incubation, which has the effect of contracting blood vessels, and tripeptide LSW, which has the effect of improving the proliferation of VSMCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the important role of ACE in hydrolyzing angiotensin I into angiotensin II under the condition of strong vasoconstriction, ACE-inhibition has always been a key target of anti-hypertensive research ( 43 , 44 ). It has been stated that ACE-inhibitory peptides have a variety of blood pressure-lowering effects other than ACE inhibition ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunction of VSMCs can be induced by Ang II and results in adverse events like increased oxidative stress, inflammation, migration, and hyperplasia, and therefore plays a key role in the pathogenesis of hypertension, restenosis, and atherosclerosis ( 46 , 47 ). The pathological proliferation and migration of VSMCs induced by Ang II are the dominative factor of vascular remodeling ( 43 ). Studies have found that antihypertensive peptides derived from egg white can inhibit migration and regulate Ang II-stimulated VSMCs ( 48 , 49 ).…”
Section: Discussionmentioning
confidence: 99%